1, 3‐Bis‐dibutylaminopropan‐2‐ol as inhibitor for reinforcement steel in chloride‐contaminated simulated concrete pore solution. Issue 12 (16th May 2012) - Liu, J. P.; Chen, C. C.; Cai, J. S.; Liu, J. Z.; Cui, G.
Abstract An organic compound, 1, 3‐bis‐dibutylaminopropan‐2‐ol (BDAP) was prepared and tested experimentally as inhibitor for reinforcement steel in simulated concrete pore solution. The electrochemical behavior of carbon steel electrodes immersed in simulated pore solutions with different concentration of BDAP was investigated by electrochemical measurements. Adsorption isotherm was determined based on the inhibition efficiency. The surface composition was evaluated via X‐ray photoelectron spectroscopy (XPS) as well in order to verify the presence and adsorption property of BDAP. The results showed that BDAP could effectively suppress the anodic process of carbon steel corrosion and the inhibition efficiency was improving with the increase of inhibitor concentration. BDAP could adsorb on carbon steel surface according to Langmuir adsorption isotherm. XPS spectrum certified the existence of BDAP on the steel surface.